Impact of gestrinone on the course of asymptomatic endometriosis. Issue 6567 (31st January 1987) - Thomas, E J; Cooke, I D
Abstract : A new drug, gestrinone, was subjected to the first double blind, randomised placebo controlled trial of any treatment of endometriosis. The disease deteriorated in eight (47%) of the 17 patients prescribed placebo (95% confidence limits 23% and 71%) compared with none of the 18 patients prescribed gestrinone (p = 0.002). There was a difference in elimination of the endometriosis in the gestrinone group compared with placebo but this was not statistically significant (p = 0.057). There was a significant difference in improvement of the disease in the gestrinone group compared with placebo (p = 0.004), confirming that gestrinone is an effective treatment of endometriosis. Endometriosis deteriorates in at least 23% of patients; as it is impossible to predict in whom this will happen, treatment appears to be warranted in all cases.